D5.5 Report on engagement of researchers 1 - Mystakopoulos, Fotis; Pablo, Virginia De; Kuchma, Iryna; Proudman, Vanessa; Vilchis, Ivonne Lujano; Uhl, Emma; Rooryck, Johan; Dvořáková, Martina; Pölönen, Janne; Klaus, Tabea (Zenodo (CERN European Organization for Nuclear Research), 2026)
Executive Summary: Deliverable D5.5 reports on the first phase of researcher engagement carried out under Task 5.3 of the ALMASI project, covering the period from January 2025 to June 2026. The task was designed as a two-phase effort: the first eighteen months were dedicated to establishing the infrastructure and relationships needed for sustained engagement, while the remaining period will be dedicated to active delivery. This report discusses the outputs of the first phase. Engagement framework established By the end of 2025, the following framework was put in place to serve the delivery phase: Workstream 1: The ALMASI Ambassador Programme was designed and launched through an open call running from 17 November 2025 to 15 January 2026. Workstream 2: The Discussion Series on Scholar-led Publishing was introduced with its first event, Reclaiming Knowledge: Why Diamond Open Access Matters, delivered on 11 December 2025 in co-operation with the Global Young Academy. A cross-work-package stakeholder mapping exercise was developed, to support both pathways by tracking opportunities for partnerships with researcher communities, infrastructure providers, and policy actors. Reach and cohort composition The response to both workstreams (the Ambassador programme and the Discussion Series) exceeded initial expectations and required substantive adaptations to the programme's design: The ALMASI Ambassador Programme attracted 155 applications from more than thirty countries and confirmed 114 ambassadors. Of these, 61 became active participants over the course of seven launch sessions held in March 2026. The Ambassador cohort was geographically weighted toward Africa, although there was representation in each of the three core ALMASI regions. Conversion rates from application to active participation were higher in Europe and Latin America than in Africa, partially offsetting the imbalance observed at the application stage. Design adaptations included shifting from competitive selection to an expression-of-interest framework, moving from one-to-one to group-based mentoring, and the introduction of a screening step in the application process. The first webinar reached 255 registrations with a geographic mix spanning Europe, Africa, Latin America, and a smaller cohort from North America and Asia, and a professional audience dominated by library and information services staff, researchers and academics, and publishing and editorial professionals. The second webinar, held on 11 June 2026 on the Publish-Review-Curate model, drew 414 registrations, with Europe and Latin America each accounting for just over a third of registrations and a substantial African contingent. Added value for researchers and publishers Drawing on the talking points articulated during the first webinar and aligned with the work of Deliverable D5.2, the report synthesises the added value of Diamond Open Access around the following themes: For researchers: access without financial barriers; rights retention and author control; equity and participation in global science; and alignment with the public mission of research. For publishers and advocates: defining Diamond Open Access through governance and ownership rather than fees alone; advocating for research assessment reform as inseparable from Diamond Open Access; pursuing rights retention at the institutional and national level; investing in shared infrastructure, training, and quality; and communicating clearly about sustainability to secure coordinated funding. Moving forward Over the next phase of the project (M18–M36), the focus will be on delivery across both workstreams: Ambassadors will engage in local and regional events, mentoring sessions, translation and co-authorship, glossary work, and advocacy through peer communication. The Discussion Series will continue beyond the second webinar, with future themes shaped by the literature on researcher engagement and by priorities surfacing within researcher communities, including peer review platforms and the role of artificial intelligence in scholarly communication. In collaboration with Task 3.1, ambassadors will contribute to sprints by developing and reviewing training materials, extending their role from outreach to active co-creation of ALMASI's educational outputs. The final report, D5.10, due in month thirty-six, will assess the outcomes of this delivery phase against the engagement targets to which Task 5.3 contributes.